Early positive approaches to support for family carers of young children with developmental disabilities: adaptation and piloting in Quebec public services - Rivard, Mélina; Boulé, Mélina; Morin, Marjorie; Abouzeid, Nadia; Chatenoud, Céline; Morin, Diane; Mello, Catherine; Gore, Nick; Bradshaw, Jill; Hastings, Richard (Frontiers in Rehabilitation Sciences, 2025)
BackgroundThis paper presents the participative research undertaken to adapt and pilot the Early Positive Approaches to Support (E-PAtS) program, originally developed and evaluated in English for use in the United-Kingdom, for implementation within Québec’s public health and social services. E-PAtS supports family carers of young children with developmental disabilities by promoting their well-being and adjustment early in their services trajectory.MethodThe program was translated into French and iteratively adapted based on feedback from six pilot cohorts conducted across four diverse clinical settings: a rural service center, an urban center, a specialized pediatric hospital, and a diagnostic clinic. These sites were selected to ensure demographic and geographic representativity of Québec’s population, and participating families also reflected a range of backgrounds. The adaptation process was grounded in community-based participatory research principles, actively involving parents, practitioners, managers, and researchers. Changes to the program’s content and delivery were made according to partner recommendations. Evaluation focused on social validity, effectiveness, feasibility, and fidelity of implementation.ResultsParticipating parents completed questionnaires and interviews, reporting improved well-being and greater confidence in self-care, indicating the program’s relevance and positive impact. Fidelity of implementation was assessed using the E-PAtS fidelity checklist, and feasibility was evaluated through session attendance logs. Both indicators were considered strong, despite the challenges posed by the COVID-19 pandemic.ConclusionFindings support the adapted E-PAtS program’s suitability for Québec’s public services, with further refinements recommended for broader dissemination. This study highlights the value of participatory approaches in adapting evidence-based interventions across cultural and service delivery contexts.